Peran UMKM Dalam Meningkatkan Kesejahteraan Masyarakat Kabupaten Solok Selatan - Siska Widyawati; Nurdawani Putri Insyani; Nurfazlin Nova (Journal on Education, 2025)
This research uses a descriptive type of research with a qualitative approach, aiming to provide an explanation of the role of Micro, Small and Medium Enterprises in improving community welfare in South Solok Regency. The indicators to measure the level of welfare are income, housing and settlement, education and health. The results of the research show that the growth of South Solok Micro, Small and Medium Enterprises from 2019 to 2023 is still experiencing ups and downs, a very significant increase occurred in the last 1 year from 2022 to 2023, namely 5.9% and was followed by several the development of welfare level indicators, namely an increase in the rate of economic growth of 4.57%, this figure is stated to be higher than the previous year. Then the growth rate of Housing and Settlements also increased from the previous year, namely 6.24%, in the education sector, namely 2.13% and in the Health sector there was an increase from the previous year, namely 7.38%.